ACCOUNTING INFORMATION SYSTEM FOR PETTY CASH FUND MANAGEMENT AT SDN 091621 PERDAGANGAN - Ambarita, Elisabeth; Santoso, Laina Tussifah (Smart Education, 2025)
Abstract : Manual management of petty cash funds at SDN 091621 Perdagangan still faces various obstacles, such as recording errors, time inefficiency, difficulties in tracking transactions, and a lack of transparency and security of financial data. This study aims to design and implement a Microsoft Excel-based accounting information system as a practical and efficient solution to improve the performance of school financial administration. The developed system is designed to record transactions, calculate balances automatically, prepare daily and monthly financial reports, and perform regular data backups. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of needs analysis, system design, development, implementation, and evaluation through system trials. The test results show that the system is able to improve work efficiency, reduce the risk of recording errors, speed up the reporting process, and improve data security and reliability. In conclusion, this system can be an effective, economical, and easy-to-operate solution for elementary school administrative staff to realize more transparent, accountable, and modern petty cash fund management.Keywords : accounting information system; efficiency; petty cash; primary school.Abstrak : Pengelolaan dana kas kecil secara manual di SDN 091621 Perdagangan masih menghadapi berbagai kendala, seperti kesalahan pencatatan, inefisiensi waktu, kesulitan dalam pelacakan transaksi, serta kurangnya transparansi dan keamanan data keuangan. Penelitian ini bertujuan untuk merancang dan mengimplementasikan sistem informasi akuntansi berbasis Microsoft Excel sebagai solusi praktis dan efisien untuk meningkatkan kinerja administrasi keuangan sekolah. Sistem yang dikembangkan dirancang untuk mencatat transaksi, menghitung saldo secara otomatis, menyiapkan laporan keuangan harian dan bulanan, serta melakukan pencadangan data secara berkala. Penelitian ini menggunakan metode Penelitian dan Pengembangan (R&D) dengan model pengembangan ADDIE yang meliputi tahapan analisis kebutuhan, perancangan sistem, pengembangan, implementasi, dan evaluasi melalui uji coba sistem. Hasil pengujian menunjukkan bahwa sistem mampu meningkatkan efisiensi kerja, mengurangi risiko kesalahan pencatatan, mempercepat proses pelaporan, serta meningkatkan keamanan dan keandalan data. Kesimpulannya, sistem ini dapat menjadi solusi yang efektif, ekonomis, dan mudah dioperasikan bagi staf administrasi sekolah dasar untuk mewujudkan pengelolaan dana kas kecil yang lebih transparan, akuntabel, dan modern.Kata Kunci : efisiensi; kas kecil; sekolah dasar; sistem informasi akuntansi.